Penerapan Metode VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) dalam Pemilihan Sales Terbaik - Lestari, Sri Poedji; Sudarsono, Bernadus Gunawan (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Sales have the role of making sales to consumers by offering certain products. This study looks at and measures the value of each sales criteria to find out the best sales in giving rewards and the selection process is carried out using an intelligence decision support system to get fair and more measurable results, in a decision support system a method approach is used to see performance. of each alternative value have. The method used in determining the best sales in this study uses the VIKOR method or the abbreviation of ViseKriterijumska Optimizajica I Kompromisno Resenje, this method measures the lowest value as a divided value in determining decision making. The results of research on 9 sales people get the best sales results with a value of 1.